2018
DOI: 10.1002/suco.201700200
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional rigid body spring method based micro‐mesoscale study of mechanical strengthening/damaging effects to concrete by frost action

Abstract: Frost damage is an important issue for service life evaluation of concrete structures in cold regions. In fact, the frost action can have both strengthening and damaging effects on the mechanical properties of concrete material, depending on several environmental and material factors, and this complexity makes the damage evaluation more difficult in the real environment. This paper aims to develop a unified model through a micro‐mesoscale approach, which can quantitatively estimate and distinguish the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…It could be found that the current model with integrating the ice-filled meso-cracks was closer to the experimental data. Besides, a previous study by Gong et al (2018) reported that the even under freezing temperature, the strength of frost damaged concrete could not go beyond the strength of intact concrete under room temperature, in case that only the ice-filled pores effect was integrated. However, current study indicated that the freezing strength of damaged concrete could be higher than the strength of intact concrete in thawing temperature by both simulation and experiment.…”
Section: Static Loadingmentioning
confidence: 97%
See 3 more Smart Citations
“…It could be found that the current model with integrating the ice-filled meso-cracks was closer to the experimental data. Besides, a previous study by Gong et al (2018) reported that the even under freezing temperature, the strength of frost damaged concrete could not go beyond the strength of intact concrete under room temperature, in case that only the ice-filled pores effect was integrated. However, current study indicated that the freezing strength of damaged concrete could be higher than the strength of intact concrete in thawing temperature by both simulation and experiment.…”
Section: Static Loadingmentioning
confidence: 97%
“…2.1 Meso-scale scheme with RBSM As introduced, the impacts of ice formation take place in different scales thus a multi-scale approach is needed. Following the scale separation by Gong et al (2018), the damaging and strengthening effects are explained.…”
Section: Basic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The de-icing agents can accelerate the frost damage of concrete; such damage has raised much concern in recent years [2]. Analytical studies have been conducted to predict the frost damage of concrete [3][4][5][6], but some discrepancies remain due to the complex of damage phenomena. In addition to salt scaling, which spoils the appearance of the concrete, more importantly, internal frost damage threatens safety.…”
Section: Introductionmentioning
confidence: 99%